The waning of the little ice age - Morgan Kelly; Cormac Ó Gráda (University College Dublin, UCD School of Economics, 2012)
The ramifications of the Little Ice Age, a period of cooling temperatures straddling several centuries in northwestern Europe, reach far beyond meteorology into economic, political, and cultural history. The LIA has spawned a series of resonant images that range from frost fairs to contracting glaciers, and from disappearing vineyards to disappearing Viking colonies. This paper takes issue with these images, and argues that the phenomena they describe can be explained without resort to climate change.
Keywords: N50; Q54; 330; climate; global warming; Little Ice Age